PENGARUH PENDEKATAN RME BERBASIS WORDWALL TERHADAP PENINGKATAN HASIL BELAJAR MATEMATIKA KELAS I SD - Bimantara, Pebriyan; Munfariqoh, Aqidatul; Rofiq, Muhammad Aunur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by low mathematics learning outcomes of first-grade elementary school students on addition material due to conventional methods. This study aims to analyze the effect of the Wordwall-based Realistic Mathematics Education (RME) approach on improving students' mathematics learning outcomes. This quantitative study used a Quasi-Experimental Control Group Design. Samples were drawn from SD Negeri 3 Botoreco (experimental class) and SD Negeri 2 Ngawen (control class). Data were collected through observations, tests, questionnaires, documentation, and interviews, then analyzed using t-test and z-test. The results showed that the Wordwall-assisted RME approach significantly improved learning outcomes. The t-test obtained tcount 22,402 > ttable 1,678, confirming individual completeness. The z-test obtained zcount 1,48 > ztable 0,735, meaning classical completeness exceeded 70%. The experimental class average score increased from 73,17 to 94,33, while the control class slightly decreased from 94,64 to 94,11. In conclusion, the Wordwall-based RME approach is more effective in improving the mathematics learning outcomes of first-grade elementary school students than the varied lecture method.